Quercetin delivery characteristics of chitosan nanoparticles prepared with different molecular weight polyanion cross-linkers. (1st September 2021) - Kim, Eun Suh; Kim, Da Young; Lee, Ji-Soo; Lee, Hyeon Gyu
Abstract: The aim of the study was to investigate the effects of cross-linkers on quercetin (QUE) absorption characteristics of QUE-loaded chitosan nanoparticles (CS-NPs). CS-NPs (461.2–482.7 nm) were prepared by ionic gelation at pH 3.5 using tripolyphosphate (367.9 Da), dextran sulfate (>15 kDa), arabic gum (AG, >250 kDa), or hyaluronic acid (HA, >1000 kDa). Mucoadhesion and cell permeation of QUE were significantly increased by positive charged CS-NPs due to interactions with negatively charged mucosal layer. Moreover, CS-AG and CS-HA NPs prepared with relatively higher MW cross-linkers exhibited significantly higher adhesion and permeation than the others. These results were verified by a cellular antioxidant activity assay; CS-AG (137.5 unit) and CS-HA NPs (126.5 unit) showed significantly higher activities after internalization into Caco-2 cells. Therefore, encapsulation within CS-NPs prepared using high MW cross-linkers such as AG and HA is found to be potentially valuable techniques for improving the QUE absorption. Highlights: Chitosan formed nanoparticles by ionic gelation with (−) charged cross-linkers. Quercetin (QUE) was encapsulated within chitosan nanoparticles (CS NPs). Mucoadhesion and intestinal cell permeation of QUE was improved by CS NPs. Cross-linker with higher MW improved adhesiveness and permeability of CS NPs. QUE within CS NPs by hyaluronic acid or arabic gum showed the highest activity.